Pengaruh Penggunaan Media Wordwall Terhadap Kemandirian Siswa Sekolah Dasar - Nur Fadilah; Supriyadi Supriyadi (Jurnal Ilmiah Global Education, 2026)
This study aims to measure the effect of using wordwall media on student independence at Waung public elementaary school. Student independence includes the ability to organize oneself, make decisions, and take responsibility without relying on others. Using a pre-experimental one-group pretest-postest design, this study involved 18 student. Data were collected through observation, tests (pretest and postest), and documentation. The results of the Wilcoxon Signed Rank Test showed a significance of 0,000 (p- <0,05) which means there was a significant difference between the pretest and postest. The effect of wordwall on student independence is quite large, with an eta-squared value of 0,90 which indicates a significant effect in increasing student initiave, responsibility, and independence. Wordwall media creates more interactive learning, encourages active student involvement, and helps the become more independent in the learning process. The results of the study support the use of wordwall in learning elementary schools.